Analysis of Increasing Employee Competence Through On-Job Training and Off-Job Training - Deddy Novie Citra Arta; Lisnawaty Pauweni; Pandu Adi Cakranegara; Olfin Ishak; Ahiar Biongan (Enrichment : Journal of Management, 2022)
The purpose of this study was to analyze the effect of on job training and off job training methods on increasing employee competence in an oleochemical company. The research design used in this study uses a quantitative associative method. Based on the results of data analysis that has been carried out in the first hypothesis (H1), which states that the on job training method has a positive and significant effect on increasing employee competence, the t-count value is 10,054 greater than the t-table value, which is 1,692, testing the second hypothesis (H2) which states that the off job training method has a positive and significant effect on increasing employee competence, the t value is 10,085 greater than the t table value, which is 1,692, which means that the on job training method and the off job training method has a positive effect and significantly to the increase in employee competence, while the R-square value obtained was 0.805 which stated that the on job training method variables and off job training methods affected increasing employee competency by 80.50% and the remaining 19.50% was influenced by the another variable.